Evaluation and Treatment of Failed Amalgam Restorations at Ibadan, Nigeria (2013)
OBJECTIVE: Failure of tooth restoration is a major clinical problem of interest to patients, dentists and employers of labour. This study was designed to find out the average life span of amalgam as well as causes and management of failed amalgam restorations at the dental center, University College Hospital, Ibadan. The distribution of new caries in patients with this condition was also investigated. MATERIALS AND METHODS: This was an interventional study conducted among consenting patients who presented with failed amalgam restoration in our conservative clinic over a threo-yonr period. Oral examination was conducted to detect primary caries and causes of failure of the restoration. Bitewing radiograph was taken where necessary. The following data were recorded: socio-demographic variables of the patients and their complaints; life span of the failed restorations and the treatment given. Summary statistics was generated. RESULTS: One hundred and forty three patients (54 males, 89 females) presented with 198 defective restorations, Sixty five (45.5%) of thpse had 118 new carious lesions which were majorly occlusal cavities (66.9%). Fractured restoration was the commonest cause of failure. Management was variable, but replacement with amalgam was the commonest treatment. The average life span of restoration was 8.3years. CONCLUSION: The average life span of amalgam restoration was 8.3years and the major cause of failure was amalgam fracture. Replacement with amalgam was the commonest treatment. WAJM 2013; 32(4): 248-253.